Fabrication of a modular hybrid chip to mimic endothelial-lined microvessels in flow conditions. (10th February 2017) - Pitingolo, Gabriele; Vecchione, Raffaele; Falanga, Andrea P; Guarnieri, Daniela; Netti, Paolo A
Abstract: In vitro microvessel models exploiting microfluidic channels have been developed to replicate cardiovascular flow conditions and to more closely mimic the blood vessels by traditionally using plasma or solvent evaporation bonding methods. The drawback of these methods is represented by an irreversible sealing which prevents internal accessibility as well as the reuse of the device. This paper presents a novel, simple, and low cost procedure to fabricate a modular and reusable chip with endotheliazed microvessels in a hybrid configuration based on poly(methyl methacrylate) and polydimethylsiloxane presenting a temporary magnetic bonding. In details, small magnets are embedded in the two poly(methyl methacrylate) substrates each of them carrying a thin polydimethylsiloxane layer which provides enhanced sealing during flow conditions as compared to conventional procedures and makes the microchannels circular as preferred in cell culture. Finally, an endothelial cell layer is formed by culturing brain endothelial bEnd.3 cells inside the proposed microchannels and characterized upon microchannel aperture, demonstrating the preservation of the cell layer.